ANALISIS DIMENSI KUALITAS TERHADAP KEPUASAN PENGUNJUNG DAN PERILAKU PURNA PENGGUNAAN FASILITAS TOURING KEBUN PABRIK TEH WONOSARI WISATA AGRO WONOSARI MALANG - DWI RETNO ANDRIANI; ARMIETA AYU IRIANTI (Universitas Sebelas Maret, 2012)
This research was conducted at ‘Wisata Agro Wonosari’, Malang in November 2010. The purpose of this study were (1) analyze the relationship between quality dimension which consist of reliability, responsiveness, assurance, empathy, and tangibles toward assessment of visitors about the quality of Tea Plantation and Factory Touring, (2) analyze the relationship between quality dimension which consist of reliability, responsiveness, assurance, empathy, and tangibles toward visitors satisfaction after using the Tea Plantation and Factory Touring on ‘Wisata Agro Wonosari’, (3) knowing the relationship between service quality and visitors satisfaction with the attitudes of visitors after using the Tea Plantation and Factory Touring on ‘Wisata Agro Wonosari’.